(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2020)
The affirmative therapy is aimed at the LGBTQI + population. The purpose of this article was to review, from the perspective of Behavior Analysis, studies that employed the affirmative therapy. Searches were carried out on the CAPES, PubMed, LILACS, PsicINFO, SciELO and MEDLINE databases. Eight review studies and seven empirical studies were selected. It was found that the studies were based on variable theoretical approaches, four of which were based on the cognitive-behavioral model. All empirical studies evaluated self-report data. The main intervention procedures included the organization of a non-punitive therapy setting and ensured that the therapist functioned as a reinforcing audience, looking to help the individual to identify aversive contingencies related to behaviors different from those expected for their biological sex, empower him to modify such contingencies, stimulate him to describe his thoughts and emotional states associated with the condition of belonging to the LGBTQI + population and encourage him to participate in support groups.